STUDY OF CONTRACT OBJECT IN MULTI-SERVICE FINANCING USING IJARAH IN ISLAMIC BANK - Kamalia Firdausi (JCH (Jurnal Cendekia Hukum), 2021)
In a case of a dispute between an islamic bank and a customer related to multi-service financing using an ijarah contract at an islamic bank, the customer is suing for the cancellation of the contract on the multi-service financing on the grounds that the object of the contract is not the object of the contract, so the contract should be null and void. However, the court decision stated that he rejected the customer's claim. This research was conducted to examine the application of sharia principles in legal considerations in court decisions regarding contract objects in multi-service financing using the ijarah contract. This research is a normative legal research using the statutory approach method. The results of this study indicate that the legal considerations in court decisions regarding the object of the contract in multi-service financing using the ijarah contract are formally correct, but materially there is still a possibility of gharar that is not in accordance with sharia principles.